The relationship between mother's employment status and the success rate of exclusive breastfeeding for infants aged 0-6 months - Eka Oktavia; Mahardika Primadani; Isne Susanti (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background:Breast milk is mother's milk that contains many benefits for infant growth. Breastfeeding for 6 months is a requirement to be said to be Exclusive Breastfeeding. The success of Exclusive Breastfeeding is one of the benchmarks in fulfilling nutrition for infants. Global coverage of Exclusive Breastfeeding in 2024 reached 48% approaching the WHO target of 50% in 2025 but in 2030 WHO increased coverage to 60% exclusive breastfeeding coverage. Because the global target increased, in Indonesia the coverage of Exclusive Breastfeeding in 2024 became 66.4%. In the Province of DIY the coverage of exclusive breastfeeding was recorded at 76.3%, while in the Wonosari II Community Health Center in 2024 the success rate reached 89.78%. The success in providing exclusive breastfeeding depends on several factors, one of which is the mother's employment status. Working mothers and non-working mothers will have an impact on the provision of Exclusive Breastfeeding. Purpose: To determine the relationship between maternal employment status and the success rate of exclusive breastfeeding. Method: This research uses a quantitative method with a descriptive design.cross section,with a total of 78 mothers with babies aged 6-24 months. The data were analyzed usingwho is square. Results:The results of the study showed that the characteristics of respondents were mothers of dominant reproductive age 20-35 years 65 (83.3%) with the employment status of unemployed mothers 17 (21.8%) and working mothers 61 (78.2%) respondents. The success of exclusive breastfeeding was 49 (62.8%) respondents and not exclusive breastfeeding was 29 (37.2%) respondents. The results of the chi square statistical test showed a p value = 0.008 <0.05. Conclusion: so it can be concluded that there is a relationship between the mother's employment status and the success rate of exclusive breastfeeding.